Actor's Personality in the Mirror of Psychodiagnostics: Past and Present (On the Example of Using the Cattell 16 PF Questionnaire) - V.S. Sobkin; T.A. Lykova (Экспериментальная психология)
The article is devoted to the comparison of the results of studies of personality traits of student-actors carried out with the help of the Cattell 16 PF questionnaire during the last 50 years. The results of the studies of 1970—1990s conducted by different authors are given. The analysis of personality traits of modern student-actors is made on the basis of the author's empirical research implemented in 2010—2023. The studies involved students of the Moscow Theater College (2010—2018, N=188), Institute of Contemporary Art (2023, N=48), GITIS (2022-2023, N=67). In all the studies under consideration, the Cattell 16 PF questionnaire was used. The comparative analysis of the factors of the Cattell 16 PF questionnaire, for which the expressed high or low values in the studies of student-actors of different years were noted, showed that the general personality characteristic of student-actors during the last 50 years is emotional sensitivity. It was revealed that student-actors of 1970-1990 showed high scores on factor M “dreaminess” indicating developed imagination and abstract thinking. In modern student-actors this factor is not expressed, they are characterized by aspiration to leadership (factor E), courage (factor H), emotional sensitivity (factor I). The reasons for the identified generational shifts are discussed: changes in the social and political situation, development of technology, growth of competition and change in the characteristics of professional acting. It is concluded that it is necessary to take into account the identified personal characteristics of student-actors in the organization of training at the university.